Correction: BteA Secreted from the Bordetella bronchiseptica Type III Secetion System Induces Necrosis through an Actin Cytoskeleton Signaling Pathway and Inhibits Phagocytosis by Macrophages. - Asaomi Kuwae; Fumitaka Momose; Kanna Nagamatsu; Yasuharu Suyama; Akio Abe (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0148387.].